OPTIMALISASI DIGITAL MARKETING SEBAGAI STRATEGI KOMUNIKASI DALAM PEMASARAN UMKM DI ERA INDUSTRI 5.0 - Satyadinatha, I Nyoman Dhani; Yasa, Komang Widya Purnama (Waisya : Jurnal Ekonomi Hindu, 2024)
Optimizing Digital Marketing as a Communication Strategy in Marketing MSMEs in the Era of Industry 5.0 will provide insight into the things that must be done by MSME players to further utilize digital media. The research method uses a qualitative descriptive approach with primary data sources obtained from Nusantara Ice Tea MSME consumers and their Website and Social Media activities. The location of this research is in Mataram City, specifically only at UMKM Es Teh Nusantara. This research discusses Digital Marketing and its Role in MSME Marketing, Industrial Transformation 5.0 and its Impact on MSME Marketing Strategies, and Optimizing Digital Marketing as a Communication Strategy in MSME Marketing. The data obtained from is sourced from 10 MSME Es Teh Nusantara Outlets. The importance of this is discussed in order to be able to provide insight to MSME players in the industrial 5.0 era regarding the use of digital marketing as a communication strategy that is able to make a significant increase in sales at low cost costs, but it is also necessary to collaborate with related parties who are creative in the field of promotion to increase product attractiveness to consumers.